2016
DOI: 10.1007/s11165-016-9527-9
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Students’ Understanding of Science and Their Socioscientific Reasoning

Abstract: Research in socioscientific issue (SSI)-based interventions is relatively new ) highlighted the need for detailed case studies that would focus on how students respond to teachers' practices of teaching SSI. This study presents case studies that investigated the development of secondary school students' science understanding and their socioscientific reasoning within SSI-based learning environments. A multiple case study with embedded units of analysis was implemented for this research because of the contextua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
3
19
0
1
Order By: Relevance
“…Recently, using SSI in science classrooms has captured the international spotlight, as it provides a meaningful learning environment in which to engage students in scientific argument practices (Jho, Yoon, & Kim, 2014;Khishfe, 2014;Sadler, 2004;Wu & Tsai, 2010). One of the desirable outcomes of participating in the debate of SSI is the improvement of students' scientific literacy through immersing them in debates, critiques, discussions, and negotiations based on evidence (Eggert, Nitsch, Boone, Nückles, & Bögeholz, 2017;Karahan & Roehrig, 2016). As Norris and Phillips (2003) demonstrate, students can integrate and apply a derived sense (i.e., being knowledgeable about science content) and a fundamental sense (i.e., being able to read/write science texts and various modes of representation) of scientific literacy in the SSI environment.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Recently, using SSI in science classrooms has captured the international spotlight, as it provides a meaningful learning environment in which to engage students in scientific argument practices (Jho, Yoon, & Kim, 2014;Khishfe, 2014;Sadler, 2004;Wu & Tsai, 2010). One of the desirable outcomes of participating in the debate of SSI is the improvement of students' scientific literacy through immersing them in debates, critiques, discussions, and negotiations based on evidence (Eggert, Nitsch, Boone, Nückles, & Bögeholz, 2017;Karahan & Roehrig, 2016). As Norris and Phillips (2003) demonstrate, students can integrate and apply a derived sense (i.e., being knowledgeable about science content) and a fundamental sense (i.e., being able to read/write science texts and various modes of representation) of scientific literacy in the SSI environment.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…The students recognized various factors that contributed to the complexity of the SSI, which included the involvement of different stakeholders, conflicting interests of upstream and downstream communities, and economic consequences of the proposed resolutions. Karahan and Roehrig's (2017) study also indicated that the position students took concerning the Minnesota River SSI appeared to influence their ability to engage in perspective-taking. For example, students taking a biased position tended to explain the issue from a single perspective (e.g., from scientific studies or personal experiences) while other students who took a neutral position were able to explain the issue from multiple perspectives.…”
Section: / 27mentioning
confidence: 88%
“…These authors found that structuring SSI instruction to include interdisciplinary within-and across-group collaboration and confrontation among individuals promoted an increase in the variety of perspectives shared and in the diversity of approaches to resolving the SSI, and resulted in higher levels of reasoning. Karahan and Roehrig (2017) conducted a multiple case study in which they demonstrated the diverse and sometimes inconsistent ways twelve students expressed SSR when they were instructed about SSI focused on the erosion and pollution of the Minnesota River. The students recognized various factors that contributed to the complexity of the SSI, which included the involvement of different stakeholders, conflicting interests of upstream and downstream communities, and economic consequences of the proposed resolutions.…”
Section: / 27mentioning
confidence: 99%
“…One of the primary goals was to enable students to use their understanding of science to make informed decisions about SSIs that impact their lives. We found that involvement in a curriculum focused on SSIs related to environmental issues within the MRB improved secondary students' (i) environmental literacy (Karahan & Roehrig, , ), (ii) understanding of scientific practices, cultural and social influences on science, and scientific bias (Karahan & Roehrig, ), and (iii) ability to make informed decisions on environmental issues by applying multiple modes of reasoning (Karahan et al, ; Karahan & Roehrig, ). Earth systems‐oriented approaches focus on promoting understanding of complex scientific phenomena including those found within the MRB.…”
Section: Collaborative Integration Of Scientific Understanding Into Cmentioning
confidence: 99%